Estrogen receptor β and epidermal growth factor receptor as early-stage prognostic biomarkers of non-small cell lung cancer - Mauro, Laura Valeria (2010)
As 20% of stage I NSCLC patients develop recurrent and often incurable cancer, the identification of prognostic markers has a meaningful clinical application. The biological significance of steroid hormone and EGF receptors, able to regulate key physiological functions, remains elusive in NSCLC. Our aim was to investigate the prognostic input of estrogen receptors (ER·, ERß), progesterone receptors (PR) and EGFR in tumors from 58 stage I NSCLC patients. Antigen expression was analyzed by immunohistochemistry. Prognostic evaluation was performed with the multivariate Cox model. We found that about 70 and 40% of samples expressed ER· or ERß at cytoplasmic or nuclear level, respectively. Besides, only 12.1% of samples weakly expressed nuclear PR and 62.7% showed membrane EGFR staining. Correlation studies indicated an inverse association between EGFR expression and smoking status (p<0.01). Multivariate studies showed that the lack of nuclear ERß or the loss of EGFR expression were independent prognosis markers associated with shorter overall survival. We also found that patients whose tumors were negative for these two biomarkers presented the worst outcome. In conclusion, our findings could be useful for selecting stage I NSCLC patients with poor prognosis to apply an earlier treatment that impacts on survival.